Indonesian students’ social-emotional competencies and their english academic achievement - Ganda Wirajaya; Lingga Agustina Suganda; Zuraida Zuraida (Intelektual Pustaka Media Utama, 2019)
In Indonesian secondary schools, young learners might have some difficulties such as lack of motivation, lack of confidence and disengagement in learning English, which contribute to the level of their social-emotional competencies (SEC). This study was conducted to investigate the relations between 103 seventh graders’ SEC and their English academic achievement. This study provided not only the correlation but also the results of the students’ SEC, their English academic achievement, and the contribution of the students’ SEC to their English academic achievement. The collected data from the SEC questionnaire and documentation were analyzed by using Pearson Correlation. The results highlighted that there was a significant weak correlation (r-obtained=0.367) between the students’ SEC and their English academic achievement. Moreover, there was 12.6% contribution of the students’ SEC to their English academic achievement. Therefore, it is possible that social-emotional competencies may enhance students’ English academic performance.